2012
DOI: 10.1186/1824-7288-38-40
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and misconceptions of primary care physicians regarding fever in children: a cross sectional study

Abstract: BackgroundFever is an extremely common sign in paediatric patients and the most common cause for a child to be taken to the doctor. The literature indicates that physicians and parents have too many misconceptions and conflicting results about fever management. In this study we aim to identify knowledge, attitudes and misconceptions of primary care physicians regarding fever in children.MethodsThis cross-sectional study was conducted in April-May 2010 involving primary care physicians (n=80). The physicians we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 69 publications
4
58
0
13
Order By: Relevance
“…[1,2] Furthermore, there is confusion about how and whether to manage fever. Antipyretics are frequently prescribed or purchased over-the-counter (OTC), specifically to bring down body temperature in an ill child, [2][3][4][5] paracetamol and ibuprofen being the most frequently purchased OTC medicines for children. [3] Although fevers are often a presenting symptom of a self-limiting viral infection, they are also associated with serious bacterial infections, such as meningitis and pneumonia, and other non-infective illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Furthermore, there is confusion about how and whether to manage fever. Antipyretics are frequently prescribed or purchased over-the-counter (OTC), specifically to bring down body temperature in an ill child, [2][3][4][5] paracetamol and ibuprofen being the most frequently purchased OTC medicines for children. [3] Although fevers are often a presenting symptom of a self-limiting viral infection, they are also associated with serious bacterial infections, such as meningitis and pneumonia, and other non-infective illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…However, mothers should realise that sleeping children should not be awakened solely to administer antipyretics. 39 Parents should also know that tactile temperature taking practice has shown to be an inaccurate screening test for fever. Inadequate awareness about the potential harm of antipyretics is particularly alarming because, even if antipyretic drugs are demonstrated to a great extent to be safe and efficient, there are reports that their misuse may lead to possible toxic effects.…”
mentioning
confidence: 99%
“…A cross sectional study carried out in 2010 by Demir and Sekreter among 80 primary care physicians in Turkey found that only 10% of physicians knew the definition of fever, only 26% considered signs and symptoms other than fever to prescribe antipyretics and that 85% prescribed antipyretics to control fever or prevent complications of fever, especially febrile seizures 10 . The present study found that 27.5% knew that the normal axillary temperature was 34.7°C to 37.3°C (94.5°F to 99.1°F).…”
Section: Discussionmentioning
confidence: 99%